Analysis of Islamic Law Reform Methods in KUPI Fatwa No. 02/IV/2017 Concerning Child Marriage - Abdul Wahid Maksum (Al Mashaadir : Jurnal Ilmu Syariah, 2025)
Child marriage is a serious problem in the social, cultural, and legal realms in Indonesia, even though there has been a revision of the minimum age limit for marriage through Law No. 16 of 2019. This practice is still ongoing and is often legitimized with religious postulates. The fatwa of the Indonesian Women's Ulema Congress (KUPI) No. 02/IV/2017 was present as a critical response to this condition, stating that child marriage is haram because it is contrary to the principles of sharia maqashid, especially the protection of soul, intellect, and offspring. This article analyzes the legal basis and method of Islamic law reform used in the fatwa, using a descriptive-analytical qualitative approach and content analysis of fatwa documents and related literature. The results of the study show that this fatwa prioritizes a contextual approach, sharia maqashid, and collective ijtihad of women scholars, as well as integrating the values of gender justice and child protection as the main foothold. This fatwa not only contributes to the discourse on Islamic law reform, but also becomes an instrument of moral advocacy in fighting for children's rights and strengthening social movements to abolish the practice of child marriage.